Research progress on direct pulp capping of primary teeth - YU Jinjin; ZHU Jianhui; WU Zhifang (口腔疾病防治, 2024)
The timely treatment of dental caries and pulp disease in primary teeth holds significant importance for maintaining children's oral health. Direct pulp capping (DPC) is a vital pulp treatment that involves covering the exposed pulp with bioactive materials to promote dentin bridge formation. DPC is commonly used in primary teeth with vital pulp and mechanical pulp exposure not exceeding 1 mm. DPC offers advantages such as minimal invasiveness, comfort, simplicity of operation and short chair-side time, making it suitable for pediatric dental clinical practice. Early studies suggested negative treatment outcomes for DPC in primary teeth with carious pulp exposure. Over the years, there have been advancements in materials and technology demonstrating positive outcomes in the clinical research of primary teeth with deep caries. However, due to the limited quality of related studies, DPC has not been widely recommended for the treatment of primary teeth with carious pulp exposure, and its widespread use needs further support by more high-quality evidence-based medical research. The success rate of DPC in primary teeth is influenced by factors including pulp status, clinical operations (such as isolation and caries removal), pulp capping material, cavity type, tooth position, coronal sealing, and dental fear. In clinical operation, dentists should accurately assess pulp status and minimize bacterial contamination. Mineral trioxide aggregate (MTA) is a DPC agent with relatively sufficient evidence and good therapeutic effects, and the crown should be tightly sealed after pulp capping. Additionally, the effects of novel biocompatible materials such as iRoot BP Plus used in DPC of primary teeth, and the influence of other factors like hemostatic methods on the prognosis of affected teeth, need further exploration.